2009
DOI: 10.1128/cvi.00013-09
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of a Combination of Korean Red Ginseng and Highly Active Antiretroviral Therapy in Human Immunodeficiency Virus Type 1-Infected Patients

Abstract: To determine whether Korean red ginseng (KRG) has beneficial effects on human immunodeficiency virus type 1 (HIV-1)-infected patients administered highly active antiretroviral therapy (HAART), we analyzed the CD4 T-cell count, viral load, and resistance mutations to HAART in 46 individuals. Thirteen patients harbored resistance mutations at baseline. The study population was divided into two groups: specifically, a group treated with a combination of HAART plus KRG (23 patients) and a group treated with HAART … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 24 publications
(25 reference statements)
1
27
1
Order By: Relevance
“…In ad-dition, the frequency of a gross deletion in the 5'-LTR/ gag in these KRG-treated patients was 2-fold higher than that of the g∆nef [20]. With KRG treatment alone, several patients among less than 100 HIV-1 infected patients diagnosed prior to 1991 remained healthy for 20 years after diagnosis [20,21], and we recently showed that combined treatment with HAART plus KRG was more beneficial than HAART only [22].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In ad-dition, the frequency of a gross deletion in the 5'-LTR/ gag in these KRG-treated patients was 2-fold higher than that of the g∆nef [20]. With KRG treatment alone, several patients among less than 100 HIV-1 infected patients diagnosed prior to 1991 remained healthy for 20 years after diagnosis [20,21], and we recently showed that combined treatment with HAART plus KRG was more beneficial than HAART only [22].…”
Section: Introductionmentioning
confidence: 83%
“…The daily dose of KRG was 5.4 g for men and 2.7 g for women [22]. On averfor men and 2.7 g for women [22].…”
Section: Therapy With Korean Red Ginsengmentioning
confidence: 99%
“…Ginseng saponin is a major component of ginseng extract, and a glycoside of ginseng saponin known specifically as ginsenoid is regarded as an active component responsible for various beneficial effects of ginseng. [25][26][27][28] Red ginseng is produced by steaming and drying fresh ginseng, which results in chemical changes of ginsenoids are reported (Cyto c-c), cleaved caspase-3 and -9, and Bcl-2 are blocked by antioxidants, N-acetyl cysteine (NAC, 5 mM), NOX inhibitor (NOXi, 1 mM), and MitoQ (1 mM) at 6 and 24 h. Representative western blots (a) and quantitation graph at 6 and 24 h (b, c) are shown. b-Actin is used as control.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Various beneficial pharmacological effects of ginseng or its components have been reported, including anticancer, anti-allergy, antiinflammatory, antifatigue, antistress, and immunomodulatory activities. [5][6][7][8][9][10][11][12][13][14][15][16] In clinical studies, ginseng has been shown to have beneficial effects on improving the survival and the quality of life among breast cancer patients, 17 in a placebocontrolled pilot trial of cancer patients, 18 in patients infected with human immunodeficiency virus, 19,20 and on reducing the occurrence of gastric cancer. 21 Immunomodulatory effects are among the beneficial properties attributed to ginseng extract.…”
Section: Introduction Imentioning
confidence: 99%